Legal Education for Medical Students in the New Era: Generative Logic, Practical Challenges, and Optimization Pathways - Xiang, Xinyi; Lu, Lu; Zhai, Yuanming (Journal of Social Science and Humanities, 2026)
Comprehensively advancing the rule of law in healthcare is an inalienable part of the national strategies. Medical students are the main force of medical and health undertakings in the future. The standard of legal education is closely associated with the prevention and resolution of medical disputes, the harmony of doctor-patient relationships, and the perfection of the healthcare legal system. Under the background of the new era, this paper expounds the generation logic of medical students’ rule of law education, and reveals its inevitability from three dimensions: the requirements of China’s national rule of law construction, the internal needs of medical model transformation, and the realistic demands of medical professional risk prevention. Our analysis has found out the key difficulties which exist in top-level design, curriculum contents, teaching methods, teacher team, and evaluation systems. At last, an optimized route is put forward, which merges ethics and law within a whole-person education pattern, taking medicine-law combination as the core, to promote education quality and cultivate the growth of high-level medical specialized persons.